The Effect of Chemistry and 3D Microstructural Architecture on Corrosion of Biodegradable Mg–Ca–Zn Alloys. Issue 11 (30th June 2021) - Zander, Daniela; Zaslansky, Paul; Zumdick, Naemi A.; Felten, Markus; Schnatterer, Christian; Chaineux, Veronika F.; Hammel, Jörg U.; Storm, Malte; Wilde, Fabian; Fleck, Claudia
Abstract : The development of biodegradable Mg–Ca–Zn alloys strongly relies on the understanding of the varying 3D microstructural architectures by means of high‐density‐resolution imaging, such as synchrotron radiation–based X‐ray microtomography (SR‐μCT). The development of useful strategies to control the degradation process, including the design of appropriate 3D microstructures, focusing on the type, fraction, morphology, distribution, connectivity, and interfaces of different phases, depends on a comprehensive understanding of the underlying corrosion processes. SR‐μCT enables the nondestructive analysis of the same microstructure within a volume exposed to different immersion times in artificial physiological solutions, e.g., Hanks' balanced salt solution without glucose (HBSS). In this work, quantitative 3D imaging via SR‐μCT demonstrates the formation of a continuous 3D network of secondary phases for low‐alloyed Mg–Ca–Zn. Furthermore, a change in the corrosion mechanism from very localized to uniform heterogeneous corrosion processes is observed. This mechanistic change is associated not exclusively with the electrochemical activity of the primary α‐MgSS and the secondary (Mg, Zn)2 Ca and Mg–Ca–Zn phases, but also with their volume fraction, distribution, 3D morphology, connectivity, and the formation of corrosion product layers. Abstract : The effects of chemistry and 3D‐microstructure architectures were investigated in Hanks' solution via quasi in situ synchrotron radiation‐based X‐ray microtomography, in order to gain a comprehensive understanding of the corrosion processes of Mg–Ca–Zn alloys. Quantitative 3D imaging shows the formation of a varying continuous 3D network of secondary phases and a subsequent change in the corrosion mechanism.